2021
DOI: 10.1016/j.rmcr.2021.101450
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment with afatinib following the failure of osimertinib rechallenge with osimertinib-induced interstitial lung disease: A case report

Abstract: Herein, we report the case of an 84-year-old woman with epidermal growth factor receptor ( EGFR ) mutation exon 19 deletion postoperative recurrent lung adenocarcinoma. Osimertinib was administered as a first-line treatment; however, she was urgently admitted to our hospital due to dyspnea on the 46th day. Chest computed tomography revealed bilateral diffuse ground-glass opacities (GGOs) suggestive of grade 3 osimertinib-induced interstitial lung disease (ILD). After discontinuation of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…Targeted therapy has become an important treatment method for NSCLC, and EGFR-TKIs have provided a good therapeutic effect for NSCLC patients with EGFR mutation [ 9 ]. However, after taking EGFR-TKI, patients may need to stop or change their medicine due to drug resistance [ 13 , 14 ], ILD [ 5 , 15 ], and so on, just like the patient we reported. The most common mechanism of acquired resistance is EGFR T790M mutation, which affects the use of first- and second-generation EGFR-TKIs [ 13 ], while third-generation EGFR-TKIs, such as osimertinib, have good efficacy in T790M positive patients [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…Targeted therapy has become an important treatment method for NSCLC, and EGFR-TKIs have provided a good therapeutic effect for NSCLC patients with EGFR mutation [ 9 ]. However, after taking EGFR-TKI, patients may need to stop or change their medicine due to drug resistance [ 13 , 14 ], ILD [ 5 , 15 ], and so on, just like the patient we reported. The most common mechanism of acquired resistance is EGFR T790M mutation, which affects the use of first- and second-generation EGFR-TKIs [ 13 ], while third-generation EGFR-TKIs, such as osimertinib, have good efficacy in T790M positive patients [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 81%
“…Therefore, timely intervention is very important. The majority of reported cases, including our case, successfully controlled OsiILD by discontinuing or reducing osimertinib and treating it with corticosteroids [ 5 , 15 , 27 , 28 , 30 , 32 35 , 37 , 38 ]. It has also been reported that OsiILD can be successfully controlled by nintedanib [ 36 ], so the use of nintedanib to control OsiILD can be considered in patients who are not suitable for corticosteroid therapy.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations